The Big Time - Warner, David and Mcgee, J. V.; Illustrated by Faber, Jules (Australia Simon & Schuster, 2015)
Davey Warner and his friends have been selected to play cricket for the local rep team. Davey's ecstatic, but the training clashes with his dog Max's obedience school. How can Davey keep his promise to his mum that he'll train Max and keep playing for the South-East Slammers?
Include Illustrations
Keywords: Australia -- Cricket players -- Cricket stories